2011
DOI: 10.1002/pmic.201100127
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in rat plasma proteome in response to high‐fat diet

Abstract: Knowledge of gender differences is important because nutritional recommendations on the basis of data collected using predominantly male subjects may not be valid for women. In the present study, we performed proteomic analysis in plasma of rats fed a high-fat diet (HFD) using 2-DE combined with MALDI-TOF-MS for analysis of differential regulation patterns between male and female plasma proteins. Male rats gained more body weight with increased values of biochemical parameters than female rats. Image analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 109 publications
1
31
0
Order By: Relevance
“…2 and 4). These results are in line with our earlier finding that Ft-A and Ft-B levels are significantly reduced in HFD-fed male rats [27]. Indeed, E2 induced similar changes in Ft-A and Ft-B expression, whereas DHT induced the opposite expression patterns (Figs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…2 and 4). These results are in line with our earlier finding that Ft-A and Ft-B levels are significantly reduced in HFD-fed male rats [27]. Indeed, E2 induced similar changes in Ft-A and Ft-B expression, whereas DHT induced the opposite expression patterns (Figs.…”
Section: Discussionsupporting
confidence: 82%
“…Laughlin et al [26] reported that higher Ft-A concentrations in the blood are related to an increased risk of developing type 2 diabetes in older women, whereas they are not associated with diabetes risk in older men. In our earlier study, we found that plasma levels of both Ft-A and Ft-B are significantly lower in males after HFD feeding while remarkably higher in females [27]. Moreover, Ft-B has been shown to be up-regulated in plasma of both male and female diabetic rats [28].…”
Section: Introductionmentioning
confidence: 99%
“…Not only can proteomics describe a complete proteome at organelle, cell, or tissue levels, but it can also compare the protein profiles from different treatments and can then identify changes in protein expression levels combined with mass spectrometry and software databases [7]. The twodimensional electrophoresis (2-DE)-based proteomics remains useful in resolving protein extracts from organisms due to its high resolution and low expense [8,9]. Metabolomics can be used to characterize metabolic profiles in various biological systems including organs, tissues, biofluids, or even whole organisms [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[14]). However, after 2 weeks, body weight and food intake of the HFD rats were higher (p<0.05) than those of ND rats at all subsequent time points in both genders [14]. Total body gain per food intake of HFD fed male rats was higher in female by an average of approximately 30% (p=0.001).…”
Section: Hfd-induced Phenotypes In Male and Female Ratsmentioning
confidence: 99%
“…In our previous studies, we investigated genderdependent protein expression in plasma [14], skeletal muscle [15], brown adipose tissue [16], and liver [17] of rats in response to HFD treatment and found existence in clear gender dimorphism. To date, proteome profiling of adipose tissues has been established by many investigators, focusing mostly on a specific fat deposit [18][19][20].…”
Section: Introductionmentioning
confidence: 99%